A STATISTICAL ANALYSIS TO FIND OUT AN APPROPRIATE DOCKING METHOD - Kalita, Jun M; Ghosh, Surajit K; Sahu, Supriya; Dutta, Mayurakhi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The objective of the study was to determine a suitable and reliable docking protocol based on a statistical study. Methods: Statistical analysis was done to find out the co-relation between in-silico and in-vitro results. Results: All the docking method shown acceptable root mean square deviation (RMSD) value those were found to be less than that of 2 Ã…. Coefficient of co-relation value was also quite satisfactory with highest of r = 0.6574 and rs=0.8322 for LigandFit. Conclusion: Among the three docking method used for the study, LigandFit was found to be more appropriate as it shown low RMSD and high coâ€‘relation coefficient. Keywords: Dihydrofolate reductase, 1J3I, LigandFit, CDOCKER, Gold, Karl Pearson's coefficient of correlation, Spearman's rank correlation (rs).